Influence of harmful production factors on occupational morbidity of poultry workers - Kardashevska, O. I. (Journal of Education, Health and Sport, 2017)
Despite the automation and mechanization of poultry farms, an increasing percentage of workers are exposed to unfavorable production factors: dustiness, microclimate, gas content (ammonia, hydrogen sulfide, high concentrations of carbon dioxide, formaldehyde), bacterial and fungal air pollution in the working area, production noise, high humidity leading to the emergence of occupational diseases in poultry workers. Therefore the study of the structure of occupational disease in this contingent of patients is relevant and timely. The purpose of the work was to study the modern scientific trends regarding the influence of harmful industrial factors on the health of the workers of poultry farms. A retrospective analysis was conducted of the collection of publications (47 sources) of domestic and foreign authors on the occupational morbidity of the workers of the agro-industrial complex. Mineral and organic dust, unfavorable microclimate, physical overload of the neuromuscular apparatus of the upper and lower extremities, forced working posture, body tilt, pathogens of infectious and parasitic diseases, allergens, etc. are adversely affected by workers of enterprises of the agro-industrial complex. These factors cause diseases of the respiratory system, the cardiovascular system, inflammatory and dystrophic diseases of the eyelids and conjunctiva, namely: chronic bronchitis, occupational allergies, zoo anthroponomics. Potentially harmful to the health of poultry workers is a dust of a production environment of inorganic, organic and biological nature, which increases the likelihood of disease development, their progression and unfavorable prognosis. Established allergenic, fibrogenic, irritating, infectious and toxic effects of various components of dust, as well as inhibition of the natural resistance of the organism of poultry farmers. Another major air pollutant in industrial premises is microbial aerosol. It has been found that 56% of the workers complain of headaches and dizziness, 37.3% of them are for constant undead, 42% for dryness of the nose, skin irritation. Characteristic are complaints of itching, periodic rash on the skin, dryness and peeling of the skin of the hands, coughing, and feeling of pristine in the throat. Summarizing the data of the analysis of professional literature, the range of publications is mainly devoted to issues of hygienic regulations and identification of harmful factors of production, the study of the immune, cardiovascular system and respiratory organs from the standpoint of outdated and inadequate medical conditions of labor regulations, requirements and diagnostic methods. The presented results of scientific researches are fragmentary and descriptive without a comprehensive assessment of risk factors and in-depth analysis of the pathogenetic mechanisms of dental diseases in the workers of poultry farms. Therefore, it is relevant to form a modern understanding of the dental morbidity of poultry workers.